下顎関節突起に生じた軟骨芽細胞腫の1例 - 丹沢, 秀樹; 坂本, 洋右; 鵜澤, 一弘; 神津, 由直; 笠松, 厚志; 皆川, 康之 (日本口腔外科学会雑誌, 2012)
Chondroblastoma is a rare benign tumor of the head and neck. We report a case of chondroblastoma of the mandibular condyle. A 56-year-old woman was referred to our department for the treatment of a left mandibular condyle tumor, which was detected on computed tomography （CT）. The patient had a 3-month history of intermittent pain in the left pre-auricular area, accompanied by episodic trismus and subjective swelling around the lesion. CT and magnetic resonance imaging （MRI） revealed an osteolytic defect in the anterior portion of the left mandibular condyle and a mass extending anterolaterally. The biopsy diagnosis was a chondroblastoma. We performed an en bloc resection that included part of the mandibular ramus. There has been no sign of recurrence for 26 months postoperatively.